ANALISA KEPUASAN PT. ANGKASA PURA I CABANG SEPINGGAN BALIKPAPAN TERHADAP ON TIME PERFORMANCE GROUND HANDLING AGENT - Ersania Dwi Meinita; Abdul Mu’ti Sazali; Dewi Ratnasari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Punctuality or also known as On Time Performance (OTP) has become a benchmark trust from providers (AP 1 SAMS Sepinggan Balikpapan Branch) and users (Airlines and Passengers) of the airport services. The purpose of this study is to find out the cause of the OTP has not been achieved in the performance of Ground Handling (PT. Aviako Sepinggan), to find out what efforts have been made by PT. Aviako Sepinggan to achieve OTP in order to meet the satisfaction of PT. Angkasa Pura 1 Branch SAMS Sepinggan Balikpapan, knowing the efforts to maximize existing human resources to achieve the expected OTP, as well as knowing the solutions obtained to fix existing problems. The research method used is by using a qualitative descriptive method. For data collection using the method of observation, interviews, literature study, and documentation. The theoretical basis used in this research is based on Doc 10121 Manual On Ground Handling and IATA Airport Handling Manual. From the results of the research that has been done, it can be seen that the available conveyors are still not evenly distributed, the Human Resources training has not been carried out optimally, and the lack of supervision from the supervisor of ground handling activities. With the even distribution of conveyor machines, conducting regular training to ground handling personnel regarding their duties and responsibilities, as well as optimizing supervision of the implementation of ground handling activities to achieve OTP targets in order to meet service user satisfaction.